Simulation Study of Class E and Receiver Circuit for Inductive Power Transfer - Anis Ashikin Binti Mohamad Fadzli; NOREZMI JAMAL; RASIDA NORJALI1; NORAIN SAHARI; SHAKIR SAAT (Progress in Engineering Application and Technology, 2024)
This paper presents a circuit simulation of the transmitter and receiver side for an Inductive Power Transfer (IPT)--based application. A key issue of the IPT system is to produce a higher output power at the receiver side due to several losses such as switching losses, gap losses, and parasitic losses. To tackle the issue of switching losses at the transmitter side, a Class E circuit was proposed to energize the transmitter coil efficiently. Specifically, the IPT system's performance worked at 1MHz operating frequency and 9V DC supply voltage. In contrast, the rectifier and buck-boost circuit were used at the receiver side of the IPT system. The proposed circuit is validated through LTspice software. The results revealed that the Class E circuit could achieve an efficiency of 90% at the transmitter side, while the output voltage at the receiver is about 9 Vp-p, which is much lower than the voltage at the transmitter side. Thus, the proposed circuit is significant for portable IPT-based charging circuit applications without hassle wire.